Fenomena dan Kecepatan Minimum Fluidisasi - Widayati Widayati (Eksergi, 2010)
Phenomenon and the minimum fluidization velocity (Umf) solid-gas depend of particle type, gas flow rate, column diameter and height of solids bed. This research was conducted on sand of quartz, iron and volcano Merapi (group B the particle) in the column with 6 cm diameter and height of the bed that varies are 6 cm, 8 cm and 10 cm. Observations began after the air with the lowest velocity flow from the bottom upwards through the bed. From the observations obtained a phenomenon that occurs is the fixed bed, bubbling fluidization and slugging fluidization. Umf in the height of bed 6 cm were 10.3 cm/sec, 7.3 cm/sec and 4.8 cm/sec. While at the height of bed 8 cm were 11.9 cm sec, 7.3 cm/sec and 5.1 cm/sec. and at the height of the bed 10 cm value (Umf)  obtained were 8.8 cm/sec, 8.8 cm/sec and 5.8 cm/sec. Based on theoretical, the Umf  for quartz sand was 12.0 cm/sec, iron sand 16.2 cm/sec and sand volcano Merapi 12.3 cm/sec. Thus, the value Umf, an experiment that comes closest to the value Umf theory only occurs for the use of quartz sand column diameter of 6cm and 8cm height of the bed.